Autoritarismo, tecnocracia e natureza: representações da pátria brasileira em o fruto do vosso ventre, de Herberto Sales (1976) - Soares, Fernanda Pereira (2013)
This research raises questions about the work of the writer Herberto Sales called O fruto do vosso ventre, published in 1976, with the goal to analyze how the civil military dictatorship was represented in this novel and how the Brazilian national identity was reworked in this fiction. Thus, the literary field of this age was approached, to understand in what context this novel is inserted and yours connections with the censure and the governments agencies of the time. Then, analyzes one slope of Latin American literature and the specific language of this novel, to locate the work thematically. Lastly, the mosaic allegorical created by Sales is explored through analysis of the works it served as reference, like the Carta de Pero Vaz de Caminha, Iracema by José de Alencar and 1984 by George Orwell. The theoretical basis of this work relied mainly in the writings of Benedict Anderson, Mikhail Bakhtin, Tzvetan Todorov, Herbert Marcuse, Dante Moreira Leite, Marilena Chaui.